Efficient Genotyping Workflow for Accelerating Maize Improvement in Developing Countries - CGIAR Research Program on Maize (2021)
Validated: Scientists showed how deploying an in-house genotyping platform alongside optimized molecular techniques can accelerate maize improvement activity for a quick result turnaround—providing a workflow that can also be adopted by less sophisticated breeding laboratories in developing countries for efficient crop improvement.